2002
DOI: 10.2176/nmc.42.332
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Subfalcial Transcallosal Migration of a Missile to the Contralateral Hemisphere Causing Deterioration in Neurological Status. Case Report.

Abstract: A 26-year-old man sustained a gunshot injury. Computed tomography (CT) demonstrated the missile in the right parietal region. Twenty-four hours later, the missile had moved towards the midline. Following slight deterioration in his neurological condition one week later, follow-up CT revealed that the missile had crossed the midline through the corpus callosum and was located in the left parietal region. CT during the second week demonstrated that the missile had stopped close to the left parietal bone. Spontan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 5 publications
(9 reference statements)
0
7
0
Order By: Relevance
“…Our group has demonstrated that BDNF levels were decreased in manic and depressed BPD patients [31] and this was negatively correlated with manic symptoms [32]. Of note, BDNF has been involved in memory and learning [33], and trophic actions, such as altered neuronal plasticity and cellular morphology while CREB is a transcription factor and one of the genes regulated by the cAMP-CREB cascade is BDNF [34].…”
Section: Discussionmentioning
confidence: 93%
“…Our group has demonstrated that BDNF levels were decreased in manic and depressed BPD patients [31] and this was negatively correlated with manic symptoms [32]. Of note, BDNF has been involved in memory and learning [33], and trophic actions, such as altered neuronal plasticity and cellular morphology while CREB is a transcription factor and one of the genes regulated by the cAMP-CREB cascade is BDNF [34].…”
Section: Discussionmentioning
confidence: 93%
“…Four mechanisms might account for bullet/bullet fragment migration after a GSWH: bullets are present in the ventricular system, fragments are present in the necrotic liquefied brain tissue, projectiles travel along the trajectory of the crushed brain tissue, and intact heavy fragments sink due to gravity [ 9 , 10 ]. In the present case, one fragment moved in liquefied brain tissue due to gravity; another moved in the direction of the point of entry, following cerebral softening and local tissue damage along the injury trajectory.…”
Section: Discussionmentioning
confidence: 99%
“…Our understanding of physics of missile injury explains the difference in severity and clinical presentation, the type of weapon and trajectory of bullet before and after brain penetration being the most likely distressing factors [5]. Migration of these bullets is not so common in literature with a consensus about significant sequences of this event [6,7], while crossing midline twice (at time of injury and during migration)has additive effect on morbidity [8,9].…”
Section: Discussionmentioning
confidence: 99%